Beneficial Effects of Resveratrol-Mediated Inhibition of the mTOR Pathway in Spinal Cord Injury - Jingying Zhou; Xue Huo; Benson O. A. Botchway; Luyao Xu; Xiaofang Meng; Songou Zhang; Xuehong Liu (Neural Plasticity)
Spinal cord injury (SCI) causes a high rate of morbidity and disability. The clinical features of SCI are divided into acute, subacute, and chronic phases according to its pathophysiological events. The mammalian target of rapamycin (mTOR) signaling pathway plays an important role in cell death and inflammation in the acute phase and neuroregeneration in the subacute/chronic phases at different times. Resveratrol has the potential of regulating cell growth, proliferation, metabolism, and angiogenesis through the mTOR signaling pathway. Herein, we explicate the role of resveratrol in the repair of SCI through the inhibition of the mTOR signaling pathway. The inhibition of the mTOR pathway by resveratrol has the potential of serving as a neuronal restorative mechanism following SCI.